The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1113/jphysiol.1984.sp015197
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamics of pelvic nerve induced penile erection in the dog: possible mediation by vasoactive intestinal polypeptide.

Abstract: SUMMARY1. The haemodynamics of erection were elucidated in the anaesthetized dog by analysing in quantitative terms the changes of penile arterial inflow, venous outflow and tissue volume during graded pelvic nerve stimulation. The study also provides information on possible neurotransmitter mechanisms of the erectile response.2. Erection evoked by pelvic nerve stimulation appeared to result from two main circulatory events: first, there was a prompt dilatation of the penile 'resistance vessels', causing a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(54 citation statements)
references
References 17 publications
3
51
0
Order By: Relevance
“…Although it has been suggested that vasoactive intestinal polypeptide (VIP) is the neurotransmitter of NANC nerves in canine penile erection (Anderson et al 1984), canine penile erection induced by cavernous nerve stimulation was not abolished, but modified by VIP-anitibody (Juenemann et al…”
mentioning
confidence: 99%
“…Although it has been suggested that vasoactive intestinal polypeptide (VIP) is the neurotransmitter of NANC nerves in canine penile erection (Anderson et al 1984), canine penile erection induced by cavernous nerve stimulation was not abolished, but modified by VIP-anitibody (Juenemann et al…”
mentioning
confidence: 99%
“…4,7 Many investigators have suggested that the 28 aminoacid peptide VIP is one of the NANC neurotransmitter(s) in the trabecular smooth muscle of the corpus cavernosum. 8,9 In support of this, several observations revealed that VIP immunoreactive fibres densely innervate the trabecular smooth muscle and that VIP elicits relaxation of the trabecular smooth muscle. 10 The results of some in vivo studies demonstrated that VIP can induce an increase in ICP in various species.…”
Section: Discussionmentioning
confidence: 84%
“…Correlative in vivo investigation has provided a critical adjunct to af®rm the erectogenic effects of potential pharmacotherapies. Examples include vasoactive intestinal peptide, 62,63 prostaglandin E1, 64 apomorphine, 65 nitric oxide donors, 66 vasoactive peptides, 67 sildena®l, 29,68 nitrosylated alpha-adrenergic receptor antagonists, 69 and potassium-ATP channel openers. 70 In the course of these studies, animal models have shown the effectiveness of multiple routes of drug administration in vivo, which include General use of animal models AL Burnett intravascular, oral, topical, subcutaneous, intraperitoneal, intracorporal, intraurethral, intrathecal and intracerebral routes.…”
Section: Therapeutic Applications Of Animal Modelsmentioning
confidence: 99%
“…58 Pharmacological investigation has been applied extensively to animal models, both in relationship to novel therapeutic options and to techniques for administering therapeutic agents. Diverse in vitro methodologies using isolated erectile tissue from many animal species including bull, 59 dog, 60 rabbit, 61 rat, 62 and mouse 26,27,30 have been employed to evaluate the presence and mechanisms of action of putative erectile neurotransmitters and other effectors of the erectile response. Correlative in vivo investigation has provided a critical adjunct to af®rm the erectogenic effects of potential pharmacotherapies.…”
Section: Therapeutic Applications Of Animal Modelsmentioning
confidence: 99%